Digital-Based Teaching Material Learning Design Through Android Applications in Al Islam and Kemuhamadiyahan Courses For Non-Muslim Students With Communication Barriers at The Stkip Muhammadiyah Manokwari West Papua Campus - Dian Indriyani; Revisika Revisika; Hawa Hasan; Nurul Abidin (CV. Syntax Corporation Indonesia, 2023)
The diversity of students in higher education, there are challenges in delivering teaching materials that respect differences, including in the Al Islam and Kemuhamadiyahan courses at the STKIP Muhammadiyah Manokwari Campus, West Papua. Non-Muslim students with communication barriers need an inclusive and accessible learning approach that enables them to learn the material effectively. The purpose of this study is to identify needs, design and measure the level of validity of Digital-Based Teaching Materials in courses. The model used in the development used by researchers is the model developed by Alessi and Trollip in Mawarni and Muhtadi (2017), several stages; First, the planning stage, the goal is to define the scope, identify student characteristics, create product guidelines and collect sources; Secondly, the design stage develops idea ideas, analysis of tasks and concepts and creation of initial descriptions of products; stages of development, product manufacturing and tests and revisions. The subjects in this study were 2 people from material validators and media validators, 22 non-Muslim students of STKIP Muhammdiyah Manokwari education, and 1 lecturer. The results of material validation are very well qualified and the results of media validation are good too. Practical trials are carried out on two target users, namely the responses of students and lecturers of the supervisory courses are of good qualifications. Based on this analysis, it is concluded that digital-based teaching materials with digital book products are valid and practical to be used in the learning process in the Al Islam and Kemuhammdiyahan courses at STKIP Muhammadiyah Manokwari.